Combined modality therapy with TRAIL or agonistic death receptor antibodies - Amm, Hope M.; Oliver, Patsy G.; Lee, Choo Hyung; Li, Yufeng; Buchsbaum, Donald J. (Cancer biology & therapy, 2011)
Molecularly targeted therapies, such as antibodies and small molecule inhibitors have emerged as an important breakthrough in the treatment of many human cancers. One targeted therapy under development is tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) due to its ability to induce apoptosis in a variety of human cancer cell lines and xenografts, while lacking toxicity in most normal cells. TRAIL and apoptosis-inducing agonistic antibodies to the TRAIL death receptors have been the subject of many preclinical and clinical studies in the past decade. However, the sensitivity of individual cancer cell lines of a particular tumor type to these agents varies from highly sensitive to resistant. Various chemotherapy agents have been shown to enhance the apoptosis-inducing capacity of TRAIL receptor-targeted therapies and induce sensitization of TRAIL-resistant cells. This review provides an overview of the mechanisms associated with chemotherapy enhancement of TRAIL receptor-targeted therapies including modulation of the apoptotic (death receptor expression, FLIP, and Bcl-2 or inhibitors of apoptosis (IAP) families) as well as cell signaling (NFκB, Akt, p53) pathways. These mechanisms will be important in establishing effective combinations to pursue clinically and in determining relevant targets for future cancer therapies.